Potentially toxic metals in umbilical cord blood as a biomarker for passive smoker women - Nazila Moftian; Hossein Arfaeinia; Fereshteh Talebi; Farshid Soleimani; Sara Dadipoor; Vali Alipour; Nazanin Abdi; Nooshin Abbasi; Nastaran Taherpour; Mehdi Sharafi (Scientific Reports)
Abstract Maternal environmental tobacco smoke (ETS) exposure during pregnancy may threat the health of mothers and their newborns. The present study was performed to determine the potentially toxic metals (PTMs) in umbilical cord blood as a biomarker for passive smoker women, as well as their association with neonatal birth indicators. In total 128 mothers (exposed: 64 and non-exposed: 64) were selected as participants. A volume of 2 mL umbilical cord blood was sampled from each participant, and PTMs including As, Pb, Cr, Al, Co, Cd, Zn, Cu, Mn, Fe, Se and Ni levels were analyzed by ICP-MS. The mean concentration levels of all PTMs in exposed group was higher than non-exposed (As: 1.76, Al: 1.49, Pb: 2.57, Cd: 1.04, Cr: 1.15, Co: 1.10, Zn: 1.05, Cu: 3.41, Mn: 1.56, Fe: 1.22, Se: 1.69 and Ni: 1.03 times fold). There were statistically significant differences between the mean levels of all PTMs (except Ni and Zn) in exposed and non-exposed groups (p-value˂0.05). In exposed group, the mean of weight, height, head circumference and chest circumference of newborns were 3058.12 ± 139.23 g, 48.50 ± 0.97 cm, 34.82 ± 0.61 cm and 32.65 ± 0.20, respectively. These values in non-exposed group were 3270.48 ± 192.49 g, 50.47 ± 0.95 cm, 34.91 ± 0.60 cm and 33.14 ± 0.38 cm, respectively. Newborns of ETS exposed mothers had significantly lower weight, height, Apgar 1 min, and chest circumference at birth. With regards to the results of the present study, more comprehensive studies should be conducted in future to identify the markers of long-term exposure to tobacco smoke and tracking the biomarkers of tobacco smoke exposure in other biological matrices such as newborns blood, meconium, feces and urine.